Investigation the Annealing Temperature on Some Optical and Structural Properties of Alnico Films - Aladdin, Alaa; Kasim, Thekra; Mohammed, Awatif A (Al-Nahrain Journal of Science, 2011)
AlNiCo thin film where deposited on glass substrate by evaporation under 106 torr presses to have 2 μm thickness. The micro structure and optical properties were studied, after that the films were annelid under 103 press torr for different times at 300 oC results show that the films structure was prevent after annealing also grain size change and increase in transmission with wavelength and annealing time.